2021
DOI: 10.1007/s12011-021-03003-7
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Intestinal Microbiota in Florated Rats

Abstract: Changes in gut microbiota have shown that it plays an important role in animal health and metabolic diseases. The intestinal microbiota is a complex structure that functions as an organ system with the presence of trillions of microorganisms. In this study, changes in the intestinal microbiota of Wistar rats with high fluorine were evaluated. Water containing 100 ppm NaF was given to 14 male Wistar albino rats as drinking water for 12 weeks. Fluorine is known to be an inducer of protein oxidation, lipid peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, it has harmful effects on the liver and kidneys as well as other tissues and organs (Tkachenko et al 2021;Çetin et al 2019). Studies by many researchers have shown that oxygen radical formation and lipid peroxidation are among the harmful effects of chronic fluorosis (Chlubek and Poland 2003;Yur et al 2013;Komuroglu et al 2022). It has been reported that the use of antioxidants and antioxidantrich foods can act as an antidote in the treatment of fluorosis in the prevention of oxidative stress-induced lipid peroxidation (Samal et al 2016;Mesram et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has harmful effects on the liver and kidneys as well as other tissues and organs (Tkachenko et al 2021;Çetin et al 2019). Studies by many researchers have shown that oxygen radical formation and lipid peroxidation are among the harmful effects of chronic fluorosis (Chlubek and Poland 2003;Yur et al 2013;Komuroglu et al 2022). It has been reported that the use of antioxidants and antioxidantrich foods can act as an antidote in the treatment of fluorosis in the prevention of oxidative stress-induced lipid peroxidation (Samal et al 2016;Mesram et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide dismutase (SOD) is present in all cells that use oxygen and is aerobic. It plays an important role in defense against the superoxide radical formed as a result of the reactions (Komuroglu et al, 2021). SOD enzyme accelerates the reaction four times in biological systems (Michiels et al, 1994).…”
Section: Introductionmentioning
confidence: 99%